Microbial populations and foodborne pathogens control of mung bean sprouts - Vanichpun, Apinya (2011)
The two main objectives in this study were investigating the microbial quality and microbial communities of 'use-by date' Mung bean sprouts by using conventional culture and 16S/18S rDNA PCR-DGGE methods, and evaluating the efficacy of natural antimicrobial substances, chemical disinfectants, and thermal treatments in reducing and inhibiting the growth of the pathogens on mung bean seeds. Retail samples of pre-packed mung bean sprouts were obtained from three retailers in the local area. The microbial quality and communities were evaluated on the 'use-by date'. The highest counts of total aerobic counts (7.86 log10 CFU/g), yeasts and moulds (7.0 log10 CFU/g), total lactic acid bacteria (6.24 log10 CFU/g) and total coliforms (6.63 log10 CFU/g) were found in samples from one shop and the DGGE band sequences also identified major populations of LAB from the same samples, These indicated poor quality and spoilage of the samples from this location and could be related to improper storage at temperatures above 5°C.